Exploring novel of 1,2,4-triazolo[4,3-a]quinoxaline sulfonamide regioisomers as anti-diabetic and anti-Alzheimer agents with in-silico molecular docking simulation - Moustafa S. Abusaif; Ahmed M. Sh El-Sharief; Yehia A. Mohamed; Yousry A. Ammar; Mostafa A. Ismail; Wael M. Aboulthana; Mohamed S. A. El-Gaby; Ahmed Ragab (Scientific Reports)
Abstract In this study, a novel series of 1,2,4-triazolo[4,3-a]quinoxalines containing a sulfonamide moiety was designed and synthesized through regioselective synthesis from 2 and/ 3-hydrazino-6-(pyrrolidin-1-ylsulfonyl)quinoxaline derivatives 5 and 7. The structures of two isomers were confirmed and characterized by IR,1H NMR,13C NMR, and elemental analysis data. The synthesized 1,2,4-triazolo[4,3-a]quinoxaline derivatives 8–13 were evaluated for their antidiabetic activities by targeting α-amylase and α-glucosidase, as well as for their anti-Alzheimer activity by targeting acetylcholinesterase (AChE) at a concentration of 100 µM. Structure-activity relationship (SAR) analysis was conducted for all analogs, emphasizing the nature of the substituent groups at position one of the triazole nucleus and the positioning of the sulfonamide moiety. For α-amylase and α-glucosidase activity, the designed compounds exhibited moderate to good activity, with inhibitory percentage values ranging from 21.85 ± 0.01% to 64.70 ± 0.02% and from 23.93 ± 0.01% to 75.36 ± 0.01%, respectively. The N-allyl-[1,2,4]triazolo[4,3-a]quinoxalin-1-amine derivative 10a demonstrated the most significant inhibitory activity, with percentages of 64.70 ± 0.02% and 75.36 ± 0.01% against α-amylase and α-glucosidase, respectively, in comparison to acarbose (IP = 67.33 ± 0.01% and 57.79 ± 0.01%). Furthermore, the 1,2,4-triazolo[4,3-a]quinoxaline derivatives 8–13 exhibited low to moderate inhibitory percentages against the acetylcholinesterase enzyme, except for the 1-methyl-[1,2,4]triazolo[4,3-a]quinoxaline derivative 11b which demonstrated the highest inhibitory percentage of 44.78 ± 0.01%, compared to donepezil (IP = 67.27 ± 0.60%). Moreover, the promising derivative 10a demonstrated exceptional inhibitory activity, exhibiting IC50 values of 3.46 ± 0.06 µM and 6.89 ± 0.09 µM against α-glucosidase and α-amylase, respectively, when compared to acarbose, which has IC50 values of 4.27 ± 0.06 µM and 5.90 ± 0.09 µM. Finally, molecular docking simulations were performed for compound 10a within α-amylase (PDB: 2QV4) and α-glucosidase (PDB: 3W37), while compound 11b was analyzed within acetylcholinesterase (AChE) (PDB: 4EY7) to assess binding affinity and to explore the binding interactions with the active sites of the enzymes.